Participation of nurses in research development - Justin O. Rojaye; Robert T. Netangaheni (AOSIS, 2023)
Background: Nurses' experience in participation in research has been very diverse and culturally dependent. A shifting environment that appreciates and supports research growth necessitates studying who is involved in research and how and assessing present individual and organisational research capabilities. Aim: This study aimed to ascertain the existing research capacity among nurses in a large public hospital in Ijebu Ode, Ogun State, Nigeria, to inform the development of a programme towards building a sustainable research culture. Setting: A public hospital at Ijebu Ode, Ogun State, Nigeria. Methods: A qualitative research design was utilised. Data were collected through semi-structured interviews with 21 nurses from the general hospital. The data were then analysed thematically. Results: Participants highlighted the need for more nurses to be engaged in research development, research development problems and recommended solutions. The critical requirement was that research has a direct impact on clinical practice. Conclusion: The results from this study show that research development allows nurses to participate in research relevant to their practice and objectives. More focus should be placed on developing and implementing context-specific nursing research agendas and implementation research skills. Contribution: The overall implications or benefits to the practice (as an example) with reference to the expanded nurses' clinical knowledge in participating in research and expand nurses' clinical knowledge in participating in research.